PENGALAMAN MAHASISWA PROFESI NERS FAKULTAS KEPERAWATAN UNIVERSITAS SUMATERA UTARA DALAM MENERAPKAN PERILAKU CARING PADA PASIEN DI RUMAH SAKIT PENDIDIKAN KOTA MEDAN - Afina Muharani Syaftriani; Setiawan Setiawan (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2017)
Caring behavior is an act based on caring, affection, skill, empathy, responsibility, sensitivity and support. Provision of nursing services based on caring behavior can improve the quality of health services. Caring behavior is not only performed by nurses but also performed by students who are running the professional education phase ners in the hospital. This study aims to explore the experiences of professional students ners Faculty of Nursing University of North Sumatra in applying caring behavior in patients at Medan City Education Hospital. This research uses phenomenology design. The sampling technique used was purposive sampling with a total of ten participants. Prior to the data retrieval, the researcher proposed the ethical clearance obtained through the Research Ethics Commission of the Faculty of Nursing University of North Sumatra. This research was conducted at Faculty of Nursing University of Sumatera Utara in February 2015 until April 2015. The data obtained were analyzed by Collaizi method. This study found there are 4 themes related to the experience of nursing students of Faculty of Nursing University of North Sumatera in applying caring behavior to patients in Medan Education Hospital, that is (1) showing high caring in caring, (2) trust with the patient, (3) performing a holistic nursing action to the patient, (4) showing respect for the patient. In addition to these experiences, this study also reveals the impact of caring behavior (5 impacts) and barriers experienced by professional students in applying caring behavior (3 barriers). Given the importance of the application of caring behavior, it is recommended to the students of professional education stage ners to continue to improve caring behavior to patients. Furthermore, for nursing education institutions or hospitals can create caring behavior standards so as to improve the quality of service to patients.Keywords: professional student ners, caring behavior, hospital education